The Egyptian Regime, Al Jazeera and the coverage of Egyptian affairs post-Arab Spring: A history of hope and oppression - Cherkaoui, Tarek (The Political Economy of Communication, 2015)
As the world marked World Press Freedom Day on 3 May 2015, Al Jazeera English (AJE) interrupted its regular programming for its senior management and journalists to discuss the state of media freedom around the world (Al Jazeera English, 2015). The Qatar-based network has long championed freedom of speech in the Arab World by giving airtime to dissenters, opposition groups, and controversial figures. Al Jazeera Arabic (AJA) has made its name in the 1990s and 2000s exposing the misdeeds, human rights abuses, and corruption of Middle-Eastern regimes. This stance came with a hefty price: Al Jazeera’s anchors became persona non grata in many Arab countries, and its offices were forcibly and regularly closed throughout the Arab World. During the past two decades, strained relationships between the Qatari government and other Arab governments became the norm rather than the exception, and ambassadors were often recalled from the Qatari capital in protest against the network’s coverage. The latter’s journalistic culture struck a chord with viewers. When Al Jazeera English (AJE) was launched in 2006, it was available in more than 80 million households worldwide. By early 2012, this number had jumped to about 250 million. According to the AJE website, the channel’s programmes can be seen on television in more than 100 countries on six continents.